2010
DOI: 10.3758/s13420-010-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous discrimination reversal learning in pigeons and humans: anticipatory and perseverative errors

Abstract: Pigeons were trained on a two-choice simultaneous discrimination (red vs. green) that reversed midway through each session. After considerable training, they consistently made both anticipatory errors prior to the reversal and perseverative errors after the reversal, suggesting that time (or number of trials) into the session served as a cue for reversal. In Experiment 2, to discourage the use of time as a cue, we varied the location of the reversal point within the session such that it occurred semirandomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
160
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(178 citation statements)
references
References 28 publications
16
160
2
Order By: Relevance
“…2). Recent research has demonstrated that pigeons both anticipate upcoming shifts in the location of reinforced responses and perseverate on nonreinforced responses that were reinforced prior to said shifts (e.g., Cook & Rosen, 2010;Rayburn-Reeves et al 2011). Lacking from the body of research was an examination of whether variability in behavior would show either an anticipatory or a perseverative bias in an analogous task in which the reinforcement probability changed in the middle of a session.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2). Recent research has demonstrated that pigeons both anticipate upcoming shifts in the location of reinforced responses and perseverate on nonreinforced responses that were reinforced prior to said shifts (e.g., Cook & Rosen, 2010;Rayburn-Reeves et al 2011). Lacking from the body of research was an examination of whether variability in behavior would show either an anticipatory or a perseverative bias in an analogous task in which the reinforcement probability changed in the middle of a session.…”
Section: Discussionmentioning
confidence: 99%
“…A common procedure when working with data germane to the topic of the maintenance of behavioral variability is to omit early sessions, in which the animals would not yet have had the opportunity to learn about the relevant aspects of potentially controlling stimuli (e.g., Rayburn-Reeves et al, 2011;Stahlman & Blaisdell 2011a, b). Therefore, we report analyses using the final 20 sessions of collected data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations